Review on the implication on the control of transboundary and trade barrier animal diseases in Ethiopia - Henok Mulatu; Waziir Shafi; Henok Abebe (International Journal of Veterinary Science and Research - Peertechz Publications, 2021)
Transboundary Animal Diseases (TADs) are highly contagious diseases of livestock within the world. they need importance within the international trade of animals and animal products. With rapidly increasing globalization, associated risk of transboundary disease is emerging. They reduce production and productivity, disrupt local and national economies, and also threaten human health (zoonosis). Transboundary diseases are a priority globally, cumulative effort is required at the international level to attenuate the spread of infectious diseases across the borders. except for sub-Saharan African countries more particularly, eradication of most Transboundary animal diseases is impossible thanks to various technical, financial and logistical reasons like increased outbreaks of transboundary animal diseases droughts and market issues. In Ethiopia Transboundary animal diseases are endemic livestock diseases that cause market limits. This imposes far-reaching challenges for agricultural scientists on the critically important have to improve technologies in animal production and health so as to confirm food security, poverty alleviation and to assist the economic process. The international approach to the management of TADs is predicated on the belief that the majority is often eradicated. However, in developing countries, eradication of most TADs is difficult for a range of technical, financial and logistical reasons. General TADs combating strategies include prevention, early warning, early detection and early control.